A new species of Leptus (Leptus) (Trombidiformes: Erythraeidae) and new records of Leptus (Leptus) haitlingeri Jacinavicius, Bassini-Silva & Welbourn, 2019 for Brazil - Bassini-Silva, Ricardo (2020)
Erythraeidae Robineau-Desvoidy has 60 genera worldwide, of which Leptus Latreille has around 260 species described, with 15 of these recorded from Brazil. Here, we describe Leptus (Leptus) flechtmanni sp. n. from a cave in the state of Pará. Additional material attributed to this species is reported from other caves and also parasitizing a harvestman. In addition, SEM images and new Brazilian host records (Diplopoda and Hemiptera) are presented for Leptus (Leptus) haitlingeri from the states of São Paulo and Rio de Janeiro. http://www.zoobank.org/urn:lsid:zoobank.org:act:53EEFF0F-DD69-4B6A-A5D6-FDF73DE94A09.